1996
DOI: 10.1021/ef9502214
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Refining Step of Biodiesel Production

Abstract: The ester product of the vegetable oil−alcohol transesterification reaction (biodiesel) is the best and the most popular diesel fuel alternative. The refining of the transesterification reaction products is technically difficult and brings an extra cost. Also, the purity level of the biodiesel must conform to European Union standards for alternative diesel fuels. The target of this study was to investigate the refining of the product mixture obtained by the transesterification reaction (with an alkali catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(107 citation statements)
references
References 19 publications
3
93
0
11
Order By: Relevance
“…In order to prevent the formation of such an emulsion in the conventional water-washing practice a large amount of water must be used. Karaosmanoglu et al (1996) concluded that a minimum of 3-5 grams of water per gram of biodiesel at 50 °C were needed to efficiently remove the impurities of the fuel (3000-5000 litres of water per Ton of biodiesel). These numbers should be considered typical of once-through water-washing operations but are not representative of closed-loop water washing schemes.…”
Section: Advantages Of Adsorption In Biodiesel Refiningmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to prevent the formation of such an emulsion in the conventional water-washing practice a large amount of water must be used. Karaosmanoglu et al (1996) concluded that a minimum of 3-5 grams of water per gram of biodiesel at 50 °C were needed to efficiently remove the impurities of the fuel (3000-5000 litres of water per Ton of biodiesel). These numbers should be considered typical of once-through water-washing operations but are not representative of closed-loop water washing schemes.…”
Section: Advantages Of Adsorption In Biodiesel Refiningmentioning
confidence: 99%
“…Some reports on post-reactor biodiesel refining have dealt with classical and simple techniques of purification, e.g. water washing (Karaosmanoglu et al, 1996). Others have indicated that adsorption technologies are particularly suited for the refining of biodiesel Mazzieri et al, 2008;.…”
Section: Introductionmentioning
confidence: 99%
“…16 The conventional "wet" methods of purification involving water-washing can be replaced by "dry" purification with adsorbents or ion exchange resins. 13,17 Moreover, the solid residue obtained by this purification has to be disposed of to landfill or other applications (compost, potential animal feed additive and potential fuel). 15 The inorganic matrix Magnesol® is a synthetic adsorbent composed of magnesium silicate and anhydrous sodium sulfate.…”
Section: Introductionmentioning
confidence: 99%
“…13,17 Moreover, the solid residue obtained by this purification has to be disposed of to landfill or other applications (compost, potential animal feed additive and potential fuel).…”
mentioning
confidence: 99%
“…60 o C for methanol) were recommended (Noureddini and Zhu, 1997). After the transesterification reaction, different separation techniques to purify the biodiesel product from the other products were investigated by Karaosmanoğlu et al (1996). They concluded that the use of hot water at 50 o C in washing was the best way to obtain high purity and yield (86%) of the biodiesel product.…”
Section: Introductionmentioning
confidence: 99%